1960
DOI: 10.1017/s0021859600022620
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the production of beef from zebu cattle in East Africa II. Milk production in suckled cows and its effect on calf growth

Abstract: 1. The estimation of milk yield in a herd of suckled zebu cattle has been described.2. Milk yield was found to be relatively stable when compared with weight at calving and subsequent live-weight change.3. Under constant conditions, there was a negative correlation between milk yield and live-weight change in the cows, compared with a positive correlation when both characters were affected by seasonal changes.4. Variation in milk yield was reflected in the growth rate of the calves, but considerably greater qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

1962
1962
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 8 publications
2
7
0
Order By: Relevance
“…The similar sucking performance of male and female calves was also found by Lampkin & Lampkin (1960), who showed that cows with male calves produced the same amount of milk as those rearing female calves. This is surprising since male calves grow quicker than females, suggesting a better utilization of milk by the males.…”
Section: Discussionsupporting
confidence: 77%
“…The similar sucking performance of male and female calves was also found by Lampkin & Lampkin (1960), who showed that cows with male calves produced the same amount of milk as those rearing female calves. This is surprising since male calves grow quicker than females, suggesting a better utilization of milk by the males.…”
Section: Discussionsupporting
confidence: 77%
“…In ungulates, higher suckling performance of male calves has been reported in some studies (Clutton-Brock et al 1981Duncan et al 1984;Berger 1986;Lee and Moss 1986;I. Kojola, unpublished data in Kojola and Nieminen 1988;Wolff 1988; but see Green and Berger 1990) but not in others (Lampkin and Lampkin 1960;Fletcher 197 1 ;Tyler 1972;Stapleton et al 1980;Gauthier and Barrette 1985;Crowell-Davis 1985;Braza and Jose 1988;Festa-Bianchet 1988;Babbit and Packard 1990b). Male calves can suckle 2.5 months longer than female calves in zebu cattle (Box indicus; Reinhardt and Reinhardt 1981).…”
Section: Sex Differencesmentioning
confidence: 91%
“…As suggested by Trivers (1974) for domestic lambs, a mother could become the limiting factor in the amount of milk consumed only when production declined to a level below the calf's needs. The level of milk produced during the early stages of lactation can exceed the maximal amount consumed by the young (Wallace 1948;Thomson and Thomson 1953;Lampkin and Lampkin 1960;Peart 1968;Arman et al 1974;Robbins and Robbins 1979). In many species, the development of the mammary glands continues in early lactation and may be enhanced by a higher suckling stimulus, as was found for rats (Tucker 1981).…”
Section: Birth Size and Body Growthmentioning
confidence: 97%
“…Approximately 53 ± 1 d after calving (May 7, 2003), milk production was estimated by weigh-suckle-weigh (WSW) after an 8-h separation (Williams et al, 1979). Calf excretory (fecal and urinary) losses during suckling were considered minimal and were not collected as suggested by Lampkin and Lampkin (1960). In addition, 10 mL of blood was collected from the jugular vein of cows by venipuncture.…”
Section: Experiments 2: Cow Performance/production Studymentioning
confidence: 99%